Human neutrophils compromise the restoration-tooth interface. (November 2020) - Gitalis, Russel; Bae, Ji Hyeon; Preston, Matthew; Patel, Meet; Liu, Ziqi; Sun, Chunxiang; Stewart, Cameron; Xiao, Yizhi; Siqueira, Walter L.; Glogauer, Michael; Finer, Yoav
Abstract: Neutrophils, cells of the innate immune system, enter the mouth and release factors that are hypothesized to contribute to the degradation of tooth dentin, methacrylate resin composites, and adhesives at the restoration-tooth-dentin interface. The objectives were to characterize neutrophils' degradation towards resin composite, self-etch (SE) and total-etch (TE) adhesives, SE and TE resin-dentin interfaces and to identify proteins that could contribute to the degradation process. Neutrophils' degradation of cured resin composite, and SE and TE adhesives, was quantified by measuring the specific resin degradation by-product, bishydroxy-propoxy-phenyl-propane (bisHPPP), released after 30 days incubation of the materials with the cells. Neutrophils' degradative effect on resin-dentin interfaces was examined by recording the interfacial fracture toughness (FT), and surface analysis of the fracture mode following incubation of SE and TE miniature short-rod (mini-SR) specimens with the cells. Neutrophils increased degradation of polymerized resin composite, and TE adhesive, but not SE adhesive over 30 days ( p < 0.05). Incubation of SE and TE resin-dentin interfaces with neutrophils led to a reduction in FT over time ( p < 0.05). The effect was more pronounced for TE interfaces. Neutrophils also affected the fracture mode of SE and TE resin-dentin interfaces. Several proteins that could contribute to the degradative activity of neutrophils, including Neutrophil collagenase (MMP-8), Matrix metalloproteinase- 9 (MMP-9), Cathepsin G, Neutrophil- gelatinase associated lipocalin (NGAL) and Myeloperoxidase, were isolated. The ability of neutrophils to degrade resin, tooth dentin, and reduce the bond strength of resin-dentin interfaces suggest neutrophils' potential role in primary and recurrent caries and dental restoration failure. Graphical abstract: Image, graphical abstract